Determining the Relative Configuration of Propargyl Cyclopropanes by Co-Crystallization - Krupp, Felix; Picher, Marie-Idrissa; Frey, Wolfgang; Plietker, Bernd; Richert, Clemens (Synlett, 2020)
Determining the diastereoselectivity of new synthetic molecules can be a challenge when NMR methods fail and the compounds are difficult to crystallize. Encapsulating organic crystals can be used to overcome this challenge. Here we show that the diastereomeric configuration of racemic mixtures of propargyl cyclopropanes can be determined by co-crystallization with 1,3,5,7-tetrakis(2-bromo-4-methoxyphenyl)adamantane and X-ray crystallography. Three crystal structures are reported that unambiguously identify the products of Fe-catalyzed cyclopropanations as cis- or trans-isomers. These findings expand the scope of co-crystallization with tetraaryladamantanes as a method to determine the stereochemical configuration of organic molecules that are difficult to crystallize by themselves.
Keywords: stereochemistry; crystallization; diastereomers; structure elucidation; X-ray crystallography